Clinical Effectiveness of an Anesthesiologist-Administered Intravenous Sedation Outside of the Main Operating Room for Pediatric Upper Gastrointestinal Endoscopy in Thailand - Somchai Amornyotin; Prapun Aanpreung (International Journal of Pediatrics)
Objectives. To review our sedation practice and to evaluate the clinical effectiveness of an anesthesiologist-administered intravenous sedation outside of the main operating room for pediatric upper gastrointestinal endoscopy (UGIE) in Thailand. Subjects and Methods. We undertook a retrospective review of the sedation service records of pediatric patients who underwent UGIE. All endoscopies were performed by a pediatric gastroenterologist. All sedation was administered by staff anesthesiologist or anesthetic personnel. Results. A total of 168 patients (94 boys and 74 girls), with age from 4 months to 12 years, underwent 176 UGIE procedures. Of these, 142 UGIE procedures were performed with intravenous sedation (IVS). The mean sedation time was 23.2±10.0 minutes. Propofol was the most common sedative drugs used. Mean dose of propofol, midazolam and fentanyl was 10.0±7.5 mg/kg/hr, 0.2±0.2 mg/kg/hr, and 2.5±1.2 mcg/kg/hr, respectively. Complications relatively occurred frequently. All sedations were successful. However, two patients became more deeply than intended and required unplanned endotracheal intubation. Conclusion. The study shows the clinical effectiveness of an anesthesiologist-administered IVS outside of the main operating room for pediatric UGIE in Thailand. All complications are relatively high. We recommend the use of more sensitive equipments such as end tidal CO2 and carefully select more appropriate patients.